2020
DOI: 10.1080/0886022x.2020.1792926
|View full text |Cite
|
Sign up to set email alerts
|

Serum elabela and apelin levels during different stages of chronic kidney disease

Abstract: Purpose: The association of serum elabela (ELA) and apelin with the progression of chronic kidney disease (CKD) is unknown. We determined if serum ELA and apelin levels were associated with CKD stage. Methods: This observational study involved 60 CKD patients and 20 healthy, age-, race-, and gender-matched controls. The participants were grouped according to renal function as follows: normal control group, CKD1 group (stage-1 CKD, 20 patients), CKD3 group (stage-3 CKD, 20 patients), and CKD5 group (stage-5 CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Accordingly, Elabela treatment was recently reported to preserve the glomerular structure, to prevent renal fibrosis and to block the expression of fibrosis-related genes in the kidneys of Dahl salt-sensitive rats on a high-salt diet and deoxycorticosterone acetate/salt-treated rats (Schreiber et al, 2017;Chen et al, 2020b;Xu et al, 2020). Consistently, recent clinical data have shown, in contrast to Ape13, that the decrease in serum Elabela levels is also strongly associated with deterioration of renal function and worsening stages of chronic kidney disease (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…Accordingly, Elabela treatment was recently reported to preserve the glomerular structure, to prevent renal fibrosis and to block the expression of fibrosis-related genes in the kidneys of Dahl salt-sensitive rats on a high-salt diet and deoxycorticosterone acetate/salt-treated rats (Schreiber et al, 2017;Chen et al, 2020b;Xu et al, 2020). Consistently, recent clinical data have shown, in contrast to Ape13, that the decrease in serum Elabela levels is also strongly associated with deterioration of renal function and worsening stages of chronic kidney disease (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…The apelinergic system in circulating as well as local tissues is regulated in multiple pathophysiology conditions. Several clinical studies have reported that lower levels of circulating ELA and apelin in patients with hypertension 102‐105 and kidney disease 106‐109 . This phenomenon in clinical studies has been recapitulated by the animal experiments.…”
Section: The Antagonistic Interaction Between Prr and The Apelinergicmentioning
confidence: 74%
“…Further, compared with healthy people, serum ELA is lower in patients with diabetic nephropathy ( Onalan et al, 2020 ). In patients with CKD, the serum ELA level gradually decreases with the reduced GFR level, with the lowest values observed in patients with CKD5 ( Lu et al, 2020 ). In our study, we used rGFR to evaluate the residual renal function in patients on PD in comparison with that in patients with CKD5.…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of APLN and ELA in the human body are affected by renal function ( Dogan et al, 2018 ; Lu et al, 2020 ). Moreover, in patients undergoing PD, the changes in serum levels of ELA and APLN and factors influencing these changes remain unclear.…”
Section: Introductionmentioning
confidence: 99%